Dress her in indigo - MacDonald, John D. (John Dann), 1916-1986 (MacDonald, John D. (John Dann), 1916-1986. Travis McGee series., 2013)
Looking for the answers to the woman's disappearance among the dropouts, drug freaks, and assorted idle rich who inhabit Oaxaca, Travis McGee suspects that the girl's car accident was no accident at all.